2010
DOI: 10.2353/ajpath.2010.090578
|View full text |Cite
|
Sign up to set email alerts
|

eNOS Knockout Mice with Advanced Diabetic Nephropathy Have Less Benefit from Renin-Angiotensin Blockade than from Aldosterone Receptor Antagonists

Abstract: While blockade of the renin angiotensin system (RAS) is beneficial in treating many patients with diabetic nephropathy, some patients show a poor response. We hypothesized that the poor response of RAS blockade is attributed to inability to stimulate endothelial nitric oxide. Recently, we reported that diabetic eNOS knockout (KO) mice develop advanced diabetic nephropathy similar to human disease. Here, we tested the hypothesis that blockade of the RAS would be less beneficial in this model than in diabetic wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 30 publications
1
58
2
Order By: Relevance
“…This could result from varied genetic background, altered methods of diabetic induction (46), or the presence of endothelial NOS deficiency (18). Also, we showed that in diabetic aortas, either the contraction or 6-keto-PGF 1␣ evoked by AA was similar to that of control nondiabetic mice; however, the level of COX-1 was lower in diabetic aortas and kidneys.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This could result from varied genetic background, altered methods of diabetic induction (46), or the presence of endothelial NOS deficiency (18). Also, we showed that in diabetic aortas, either the contraction or 6-keto-PGF 1␣ evoked by AA was similar to that of control nondiabetic mice; however, the level of COX-1 was lower in diabetic aortas and kidneys.…”
Section: Discussionmentioning
confidence: 68%
“…However, some previous reports have indicated that hypertension can develop 1 or 2 wk after diabetic induction (18,46). This could result from varied genetic background, altered methods of diabetic induction (46), or the presence of endothelial NOS deficiency (18).…”
Section: Discussionmentioning
confidence: 93%
“…In the case of the former, a number of RAAS components have been found to be upregulated with diabetes in the kidneys of eNOS 2/2 mice. 51 RAAS activation has also been described in the hearts of triply deficient n/i/eNOS 2/2 mice, although the mechanisms underlying this response have similarly not been defined. 52 In this study, we observed an approximate 50% increase in renal AngII with new-onset diabetes in wild-type mice and no change in eNOS 2/2 animals.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the aldosterone antagonist spironolactone reduces blood pressure and attenuates renal injury. 93 …”
Section: Disturbances Of No Availability In Early and Advanced Diabetmentioning
confidence: 99%